Robustness Diagram with Loop and Time Controls for System Modelling and Scenario Extraction with Energy System Applications. (June 2016) - Malinao, Jasmine; Judex, Florian; Selke, Tim; Zucker, Gerhard; Adorna, Henry; Caro, Jaime; Kropatsch, Walter
Abstract: In this research, we introduce an extension of Robustness Diagrams for modelling complex systems such as energy systems. We provide a construction scheme of this extension for the inclusion of looped and time-dependent substructures for an effective modelling framework. The latter set of substructures is introduced in this work as "reset-bound subsystems". We introduce a scenario extraction algorithm to obtain behavioral profiles from the models. Lastly, we apply our scheme to create a model of a real-world energy system and use the proposed algorithm to extract a scenario describing one process done by the system being modelled.